Pengaruh pelatihan terhadap kinerja karyawan pengrajin sepatu dan sandal kulit “praktis” Magetan - E ndrawati (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2017)
This study aims to determine the effect of providing job training on the performance of employees home industry "Praktis" Magetan. The research used quantitative descriptive method. The instruments used to collect data are questionnaires or questionnaires. The result of this research indicates that there is a significant positive effect of training variable on employee performance, it is proved by regression analysis result that get Y = 14,340 +0,5307X,  that  means  if  job  training  variable  (X)  increase  by  1%,  hence  employee performance Will increase by 0.5307, if other factors are considered fixed. Test t calculationresults  obtained  tcount(9,9076)  ³ ttable(1.66691)  This  situation  can  be  said  there  isdifferent influence of training on employee performance on the Shoes and Slippers "Praktis" Magetan Leather Sandal. Thus it can be concluded that the training effect on employee performance.